(untitled) (Scientific journal of the Fergana State University, 2023)
The article gives information on the type of composite sentences with the meaning comparison in the Uzbek and English languages. This type of sentence is connected by tone using comma and is given as separate type of composite sentence in the Uzbek language. Whereas it is connected by semicolon and is generally referred as compound sentence in the English language. In this the first predicate is inconsistent with the second. This leads to the understanding of the meanings of contradiction and inconsistency between compound sentences without expressing comparative relation in languages. This type of sentence occurs mainly in the example of proverbs.